KSISTENSI HUKUM ISLAM DALAM PEMBENTUKAN HUKUM PIDANA DI INDONESIA (Lex Journal: Kajian Hukum & Keadilan, 2018)
ABSTRACTIndonesia is a legal country that has experienced such a long legal history process. The existence of law in Indonesia become a necessary in order to arrange the citizen life. Before the independence, Indonesia followed custom laws and religious laws of the society. One of them is Islamic law having lived among the Indonesian people before the freedom time. This Islamic law has lived along with the Custom Law in Indonesia and being obeyed by the society based on the awarness each individual. Therefore, it is not suprisingly that the Islamic and Custom laws have higher position than the Positive law taken from the colonial/west law. Thus, in formulating the National Law, the Islamic and Custom laws become the material sources stated in formulating a positive law. Moreover, the formulating of the National Law, including the criminal law, needs the contribution of the Islamic law as well as the Custom and West Laws. The history of criminal law development in Indonesia has filled with Islamic values, because the socialization process of the Islamic law integrated with the custom development in resolving the celriminal cases. Keyterms: The Existence of Islamic Law, Criminal Law, National Law.